The influence of external factors on the development of olfactory disorders in patients with the coronavirus disease 2019: an immunomorphological assessment - I.S. Shponka; O.M. Usova (Medičnì Perspektivi)
Olfactory disorders of various etiology are an actual problem for a large part of the adult population of the world, according to the results of conducted research, their prevalence is about 19%. Hyposmia, anosmia, or dysosmia are considered the initial symptom in more than 25% of patients, but over time they affect more than 75% of the total number of patients. The main risk factors for the development of olfactory disorders are old age, male gender, head injuries, exposure to toxic substances and infectious diseases of the upper respiratory tract. The purpose of the study is to clarify the immunomorphological features of the olfactory epithelium of the nasal cavity of patients with the 2019 coronavirus disease, taking into account the background pathological changes in the structures of this area for a better understanding of the mechanisms of the development of olfactory dysfunction during infection with the SARS-CoV-2 coronavirus, depending on the presence of aggravating factors. Autopsy material was used for the study, namely fragments of the mucous membrane of the upper parts of the nasal cavity (olfactory epithelium), obtained from 20 deceased (8 women and 12 men) aged 53 to 86 years with a diagnosis of "Coronavirus disease 2019", confirmed by laboratory (polymerase chain reaction) and olfactory disorders of various degrees in the anamnesis. Mucosal samples were stained with standard hematoxylin and eosin and using an immunohistochemical method with antibodies to neuron-specific beta-III tubulin (TuJ-1), olfactory marker protein (OMP) and angiotensin-converting enzyme (ACE-2). The distribution of expression variants of receptors to OMP, TuJ-1 and ACE-2 in sections with signs of structural rearrangement and without signs of structural rearrangement at a magnification of 200x showed a significant difference (p<0.05): the number of OMP-positive cells in sections of the olfactory epithelium of the first group on average was 43.5 in the field of view (16.0-59.0), TuJ-1-positive cells in these sections – 44.5 in the field of view (17.0-61.0), ACE-2-positive cells – 37 in the field of view (14.0-55.0), and in the samples of the olfactory epithelium of the second group, the expression of receptors to OMP was only partially positive (18 (12.0-25.0) cells), TuJ-1 – 17.5 (14.0-24.0) cells, ACE-2 – 14 (9.0-18.0) cells. That is, the occurrence of olfactory disorders under the conditions of infection with the SARS-CoV-2 coronavirus can be both de novo and against the background of previous changes in the structural elements of the olfactory area of the mucous membrane of the nasal cavity. In this case, more vivid symptoms are likely, as well as criticality and irreversibility of pathological changes.